Genome editing: slipping down toward Eugenics? - Battisti, Davide (Medicina Historica, 2019)
In this paper, I will present the empirical version of the slippery slope argument (SSA) in the field of genome editing. According to the SSA, if we adopt germline manipulation of embryos we will eventually end up performing or allowing something morally reprehensible, such as a new coercive eugenics. I will investigate the actual possibility of sliding towards eugenics: thus, I will examine enhancement and eugenics both in the classical and liberal versions, through the lens of SSA. In the first part, I will discuss the classical eugenics from a historical perspective and conclude that classical eugenics is morally deplorable; but by currently accepting genome editing I argue that it is not possible to ‘slip’ into classical eugenics. Then, I will analyze liberal eugenics: I will consider Habermas’ and Sandel’s objections to liberal eugenics and genetic human enhancement. Subsequently, I will reply to these arguments affirming that, although it is not possible to refuse any form of genetic enhancement, liberal eugenics would not consider the principles of justice, non-maleficence, and non-instrumentalization; hence, it should be considered not morally acceptable. In addition, I will support the thesis according to which the possibility of relapsing into liberal eugenics is more likely than relapsing into classical eugenics. Then, I will present a strategy that, while avoiding falling into the undesirable scenarios related to SSA, still accepts some application of germline genome editing of embryos and gametes. In such a way, I will show that even if we accept the plausibility of a certain slip into an undesirable scenario, SSA does not offer conclusive reasons to forbid any use of germline genome editing technique in both therapeutic and enhancement fields.